Abdominal X-ray in Pediatric Acute Severe Colitis and Radiographic Predictors of Response to Intravenous Steroids. Issue 2 (February 2016) - Livshits, Alina; Fisher, Drora; Hadas, Irith; Bdolah-Abram, Tali; Mack, David; Hyams, Jeffrey; Crandall, Wallace; Griffiths, Anne M.; Turner, Dan
ABSTRACT: Background: Abdominal x-ray (AXR) can identify complications in acute severe colitis (ASC) and may assist in selecting high-risk children for early aggressive treatment. We aimed to describe AXR findings in pediatric ASC and to explore radiological predictors of response to intravenous corticosteroid (IVCS) therapy. Methods: A total of 56 children with ASC were included in a multicenter, retrospective 1-year cohort study (41% boys, mean age 12.1 ± 4.2). Radiographs of responders to IVCS and those requiring second-line salvage therapy by discharge were analyzed independently by 2 blinded radiologists. Results: A total of 33 responders to IVCS were compared with 23 nonresponders. The day-3 Pediatric Ulcerative Colitis Activity Index (PUCAI) score was significantly higher in nonresponders (63 ± 16 vs 46 ± 21, P = 0.001). The mean transverse colon luminal diameter was 30 ± 16 mm in responders and 38 ± 16 mm in nonresponders ( P = 0.94). The upper range of transverse colonic diameter in children <12 years was ∼40 mm, whereas in older children it was 60 mm as accepted in adults. Ulcerations and megacolon seen on AXR were associated with nonresponse to IVCS ( P = 0.006 and 0.064, respectively). Conclusions: The presence of mucosal ulcerations and megacolon on AXR could be considered in the risk stratification of children with ASC for early aggressive treatment, together with the previously known day-3 and day-5 Pediatric Ulcerative Colitis Activity Index scores, albumin, and C-reactive protein.